2008
DOI: 10.1111/j.1467-9280.2008.02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Delay Discounting

Abstract: Lower delay discounting (better self-control) is linked to higher intelligence, but the basis of this relation is uncertain. To investigate the potential role of working memory (WM) processes, we assessed delay discounting, intelligence (g), WM (span tasks, 3-back task), and WM-related neural activity (using functional magnetic resonance imaging) in 103 healthy adults. Delay discounting was negatively correlated with g and WM. WM explained no variance in delay discounting beyond that explained by g, which sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
185
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(213 citation statements)
references
References 36 publications
13
185
1
1
Order By: Relevance
“…Thus, this task examines several of the characteristics that have been used to describe the working memory system. Moreover, updating tasks, such as the n-back procedure, are moderately (r=0.55) (Shamosh et al 2008) to highly correlated (r=0.96) (Schmiedek et al 2009) with span tasks, and both types of tasks successfully predict reasoning abilities (Schmiedek et al 2009). Nevertheless, see Kane et al (2007) for contradicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this task examines several of the characteristics that have been used to describe the working memory system. Moreover, updating tasks, such as the n-back procedure, are moderately (r=0.55) (Shamosh et al 2008) to highly correlated (r=0.96) (Schmiedek et al 2009) with span tasks, and both types of tasks successfully predict reasoning abilities (Schmiedek et al 2009). Nevertheless, see Kane et al (2007) for contradicting results.…”
Section: Introductionmentioning
confidence: 99%
“…An example of work at the computational level would be investigations that attempt to document the existence of unconscious cognitive biases that emerge during the financial decision making process, such as the overconfidence effect (Sieck & Yates, 2001) and delay discounting (Shamosh et al, 2008). Research at the third (and most basic) level of analysis examines the biological basis of financial and economic decisions.…”
mentioning
confidence: 99%
“…Promoting mental simulations of future outcomes by cueing participants with episodes in their lives corresponding to the timing of the options decreases measured discount rates (Peters and Büchel, 2010). Higher working memory capacity is associated with both lower discounting (Shamosh et al, 2008), and an increased emphasis on model-based control (Eppinger et al, 2013), while working memory training in substance misusers has been found to decrease their delay discounting (Bickel et al, 2011b).…”
Section: The Cost Of Thinking In Economic Poverty Borderline Personamentioning
confidence: 99%